Income effects on children's life satisfaction: Longitudinal evidence for England - Gundi Knies (University of Essex, Institute for Social and Economic Research (ISER), 2017)
Using longitudinal data for children aged 10-15 years living in England in 2009-2014 we test the hypothesis that income matters for children's life satisfaction. The results suggest that children are more satisfied with life the more income their family has. Income effects are larger the less income the family has and statistically significant for children from the age of 13. Overall, the effects are small and governments aiming to increase population well-being in this group may expect greater returns from addressing satisfaction gaps experienced during school holidays and focussing on British/Irish white males and females from ethnic minority backgrounds.
Keywords: I31; J13; J17; C23; 330; childhood; children; life satisfaction; happiness; quality of life research; panel data analysis